2020
DOI: 10.1097/qad.0000000000002604
|View full text |Cite|
|
Sign up to set email alerts
|

A multilevel intervention to reduce stigma among alcohol consuming men living with HIV receiving antiretroviral therapy: findings from a randomized control trial in India

Abstract: Objective: To examine the effectiveness of a multilevel intervention to reduce HIV stigma among alcohol consuming men living with HIV in India. Design: A crossover randomized controlled trial in four sites. Setting: Government ART centres (ARTCs) offering core services in the greater Mumbai area. Participants: Seven hundred and fifty two (188 per site) alcohol-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The evidence review identified 70 intervention evaluations [29–98]. The literature flow is documented below (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence review identified 70 intervention evaluations [29–98]. The literature flow is documented below (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of stressors associated with sexual health care access, we suggest integrating mental health services with sexual health interventions and care [ 41 43 ]. Sexual health services could integrate mental health components by directly providing counseling services, providing referrals to psychological services, and organizing community engagement activities for the transgender and gender diverse people [ 42 , 44 , 45 ].…”
Section: Research and Policy Implicationsmentioning
confidence: 99%